Exposing the benefits of a pedagogy of partnership in health professions education - Penelope Engel-Hills; Hilde Ibsen; Llizane McDonald (AOSIS, 2023)
Background: Literature indicates the need to prepare health professionals who are clinically competent and socially conscious. Engagement in community projects, as an extension of workplace learning, can build professional competence and social awareness. Aim: To interrogate one such engagement; an emergency first aid responder training course was orchestrated by undergraduate students studying Emergency Medical Care. Setting: The intervention was offered in response to a community need emerging from the research project being conducted in a community in the Western Cape, South Africa. Method: Qualitative data were gathered as narrative texts from participants in the intervention and student reports about their learning experience. The data were interrogated through the application of reflexive thematic analysis and the theoretical lens of asymmetrical reciprocity. Findings: The three themes that emerged were: from research to a student led intervention, deep authentic learning, and learning as a shared experience. Benefit accrued to the students and community through a partnership of asymmetrical participants. The community offered a learning experience while students offered desired skills acquisition to community members. Conclusion: Through this interaction, students learnt respect for local knowledges, and gained enhanced social awareness, in a transdisciplinary partnership, that aimed to create a learning environment where academics, students, and community members are partners in a project delivered with a core value of social justice. Contribution: A pedagogy of partnership describes an education model arising from community-based research that enabled a social programme intervention as a relevant learning project for health science students.